2021
DOI: 10.1016/j.paid.2021.111023
|View full text |Cite
|
Sign up to set email alerts
|

Malicious mind readers? A meta-analysis on Machiavellianism and cognitive and affective empathy

Abstract: This meta-analysis investigated how the antagonistic personality trait Machiavellianism (Mach) relates to cognitive and affective empathy. Due to the role of manipulation in Mach, previous research argued that Mach should go along with higher empathic ability but found negative effects very consistently. Thus, some scholars argued that individuals with high scores in Mach had empathic deficits. The current meta-analysis (70 studies, 76 samples, and 232 effect sizes) challenged both perspectives by investiga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
3
10
0
Order By: Relevance
“…These findings lend support to our proposed mediator because dehumanization is sought to bypass empathic reactions towards others (Bandura et al, 1996;Haslam & Loughnan, 2014). In the same vein, Mach was linked to lower affective empathy (vicarious experience of others' affective states), but not to empathic performance (emotion recognition skills; Blötner et al, 2021). In line with definitional aspects of Mach, Blötner et al (2021) thus concluded that Mach was related to disregard of others, but not to empathic deficits.…”
Section: Machiavellianism Bullying and Cyberbullying And Dehumanizationsupporting
confidence: 63%
See 1 more Smart Citation
“…These findings lend support to our proposed mediator because dehumanization is sought to bypass empathic reactions towards others (Bandura et al, 1996;Haslam & Loughnan, 2014). In the same vein, Mach was linked to lower affective empathy (vicarious experience of others' affective states), but not to empathic performance (emotion recognition skills; Blötner et al, 2021). In line with definitional aspects of Mach, Blötner et al (2021) thus concluded that Mach was related to disregard of others, but not to empathic deficits.…”
Section: Machiavellianism Bullying and Cyberbullying And Dehumanizationsupporting
confidence: 63%
“…In the same vein, Mach was linked to lower affective empathy (vicarious experience of others' affective states), but not to empathic performance (emotion recognition skills; Blötner et al, 2021). In line with definitional aspects of Mach, Blötner et al (2021) thus concluded that Mach was related to disregard of others, but not to empathic deficits. This substantiates our considerations on that individuals high in Mach engage in (cyber)bullying as an intentional act of harming others.…”
Section: Machiavellianism Bullying and Cyberbullying And Dehumanizationmentioning
confidence: 97%
“…Followers likely form somewhat negative attitudes toward Machiavellian leaders. For example, a recent meta-analysis showed that because Machiavellian leaders are highly motivated by their own ultimate interests, they are low in empathy [ 64 ]. In a similar vein, Frazier and Jacezko [ 65 ] showed that followers who have Machiavellian leaders have low perceptions of their leaders’ ethical leadership.…”
Section: Hypotheses’ Developmentmentioning
confidence: 99%
“…In other words, the dark triad can encourage students to carry out cyberbullying with Empathy as a mediator variable. Previous research reported that psychopathy and narcissism were correlated with low empathy Jonason et al (2013) as well as Machiavellianism had a negative relationship with Empathy, meaning that individuals with high Machivellianism had low Empathy (Blötner et al, 2021). Meanwhile, social support in previous studies reported that social support has a positive relationship with Empathy, meaning that the higher the social support for individuals, the higher the Empathy (Park et al, 2015).…”
Section: Introductionmentioning
confidence: 95%